Is my finger broken? / Shahrul Hisham Sulaiman - Sulaiman, Shahrul Hisham (Faculty of Medicine, 2023)
A right-handed 52-year-old man complained of sudden deformity over his right ring finger following a hyperflexion injury. He accidentally hyperflexed the distal interphalangeal joint (DIPJ) of his right ring finger while showering. Since then, he noticed that he had a flexion deformity and could not actively extend his ring finger at the DIPJ.